Pengaruh Inovasi dan Kreativitas terhadap Kepuasan Konsumen pada UKM Dina Kelurahan Ntobo - Yeni Afriyani; Muhajirin Muhajirin (Target : Jurnal Manajemen Bisnis, 2021)
This study aims to determine the effect of innovation and creativity on consumer satisfaction at UKM Dina, Ntobo Village. The approach used in this research is to use an associative approach. The population in this study amounted to 100 people with a sample of 100 consumers. The sampling technique used was incidental sampling, the data collection techniques used were observation, questionnaires, and literature study. Data analysis techniques used are validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation coefficient, determination coefficient, T test, and F test by using the Statistical Product and Service Solution (SPSS) version 20 program. It shows that innovation has a partial effect on consumer satisfaction at UKM Dina, Ntobo Village, creativity has partial effect on consumer satisfaction at UKM Dina, Ntobo Village, innovation and creativity simultaneously affects consumer satisfaction at UKM Dina, Ntobo Village.